THE EFFECT OF SELF-EFFICACY AND EMOTIONAL INTELLIGENCE ON PROJECT-BASED LEARNING IN VOCATIONAL EDUCATION - Rohmat Martanto; Putu Sudira; Farid Mutohhari; Muhammad Nurtanto; Melinda Astuti (Kwangsan: Jurnal Teknologi Pendidikan, 2022)
Project-based learning does not only require hard skills, but requires a balance of soft skills and student self-development. This study aims to analyze how much influence self-efficacy and emotional intelligence have on the quality of product outcomes in project-based learning and analyze the determinant factors. A total of 228 vocational education students were involved in this study. Data were collected through questionnaires measuring self-efficacy and emotional intelligence, and product evaluation observation sheets. Data were analyzed using multiple linear regression analysis and confirmatory factor analysis. The results showed that self-efficacy and emotional intelligence had a significant effect on the quality of students' products. The level of experience, social skills, and quality of materials are the determinants of each variable. Various student self-development efforts to foster self-efficacy are very important to do to improve product quality. In addition to strengthening students' emotional intelligence, it is also very important to improve the quality of project-based learning outcomes. AbstrakPembelajaran berbasis proyek tidak hanya membutuhkan keterampilan keras, tetapi membutuhkan keseimbangan soft skill dan pengembangan diri siswa. Studi ini bertujuan untuk menganalisis seberapa besar pengaruh self-efficacy dan kecerdasan emosional terhadap kualitas hasil produk dalam pembelajaran berbasis proyek dan menganalisis faktor penentu. Sebanyak 228 siswa pendidikan kejuruan terlibat dalam penelitian ini. Data dikumpulkan melalui kuesioner yang mengukur self-efficacy dan kecerdasan emosional, dan lembar pengamatan evaluasi produk. Data dianalisis menggunakan analisis regresi linier berganda dan analisis faktor konfirmasi. Hasil penelitian menunjukkan bahwa self-efficacy dan kecerdasan emosional memiliki efek yang signifikan pada kualitas produk siswa. Tingkat pengalaman, keterampilan sosial, dan kualitas bahan adalah penentu dari setiap variabel. Berbagai upaya pengembangan diri siswa untuk menumbuhkan self-efficacy sangat penting dilakukan untuk meningkatkan kualitas produk. Selain memperkuat kecerdasan emosional siswa, juga sangat penting untuk meningkatkan kualitas hasil pembelajaran berbasis proyek.